2020
DOI: 10.1016/j.stemcr.2020.10.013
|View full text |Cite
|
Sign up to set email alerts
|

A Human Retinal Pigment Epithelium-Based Screening Platform Reveals Inducers of Photoreceptor Outer Segments Phagocytosis

Abstract: Phagocytosis is a key function in various cells throughout the body. A deficiency in photoreceptor outer segment (POS) phagocytosis by the retinal pigment epithelium (RPE) causes vision loss in inherited retinal diseases and possibly age-related macular degeneration. To date, there are no effective therapies available aiming at recovering the lost phagocytosis function. Here, we developed a high-throughput screening assay based on RPE derived from human embryonic stem cells (hRPE) to reveal enhancers of POS ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…However, in vivo validation is yet to be reported. 115 Another study has also shown that a translational readthrough inducing drug named PTC124 was also able to partially restore phagocytosis in RPE cells with MERTK mutations. 116 Also, a phosphomimetic Dbl3 molecule was sufficient to rescue phagocytosis in MERTK defective RPE cells.…”
Section: Conclusion and Knowledge Gapsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in vivo validation is yet to be reported. 115 Another study has also shown that a translational readthrough inducing drug named PTC124 was also able to partially restore phagocytosis in RPE cells with MERTK mutations. 116 Also, a phosphomimetic Dbl3 molecule was sufficient to rescue phagocytosis in MERTK defective RPE cells.…”
Section: Conclusion and Knowledge Gapsmentioning
confidence: 99%
“…More recently in vitro systems revealed potential therapeutic options to enhance OSP. A high‐throughput, orthogonal assay, aimed to discover therapeutics at a broad patient spectrum, targeting the OSP process rather than specific regulators 115 . The top hit reported in the 2020 study, ramoplanin (a lipoglycodepsipeptide antibiotic), was shown to not affect phagocytosis in healthy RPE cells but was capable of rescuing OSP in RPE cells with defective MERTK .…”
Section: Conclusion and Knowledge Gapsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that small molecules and cell transplantation both exhibit potential in the treatment of AMD. Small molecules such as ABCF1, melanin, LEDGF, and ramoplanin have been developed and used to restore RPE function in phagocytosis and metabolic activity [35][36][37][38][39]. However, relatively short half-lives of small molecules have also been observed, which may hinder the application of small molecules.…”
Section: Rpe Physiology and Therapeutic Options For Amdmentioning
confidence: 99%
“…(3) Using genetic or pharmacological approaches, RPE cells can be manipulated to simulate an in vivo RPE cell-specific disease state (Tagawa et al, 2021). ( 4) Highthroughput screening platforms can be established for screening chemical and biological libraries to identify potential compounds that can rescue phagocytosis deficiencies in RPE (Schreiter et al, 2020). The current methods to quantify POS uptake by RPE cells in culture include fluorescence-based assays, such as fluorescence-activated cell sorting (FACS) (Ramarao and Meyer, 2001), fluorescence scanning (Hook and Odeyale, 1989), or immunofluorescence , which require POS to be first labeled with a fluorescent dye such as FITC, and immunoblot-based assays, where unlabeled POS can be detected using an antibody specific to POS, such as transducin (Sethna et al, 2016) or rhodopsin (Tagawa et al, 2021).…”
Section: Introductionmentioning
confidence: 99%